FROM BOODLINES TO BALLOTS: THE INTERSECTION OF FAMILY POWER AND WOMEN POLITICAL ELECTABILITY - Anisyah, Siti; Harahap, Raegen (Universitas Riau Kepulauan, 2024)
The discourse women's representation in politics has gained traction globally, including in Indonesia. While the progress made by women in the political arena deserves recognition, especially in a society where gender Stereotypes and patriarchal norms remain deeply rooted, it is crucial to acknowledge that many women still struggle to contest elections independently without relying on factors such as political dynasties, financial resources, incumbency, or family connections. This article delves into the significant role of family ties in shaping the electability of women in politics, with a specific focus on Zainab’s successful bid in the 2019 legislative election for Electora District V, Ogan Ilir Regency. Using a qualitative-descriptive research method and a library research approach, this article explores how Zainab's victory is closely linked to the influence of her family's prominent status, which is known as a respected and generous family with extensive networks among community leaders in various villages. We foud that Zainab’s family played a crucial role in crafting a positive public image, boosting her popularity, and ultimately securing her electability, despite her status as a newcomer in the political landscape of Ogan Ilir. The findings underscore the importance of family legacy as a powerful political asset, highlighting how the strength of a family name can be a decisive factor in political success, as evidenced by Zainab’s victory in the 2019 election in Ogan Ilir Regency.